Precautionary Savings in the Great Recession - Mody, Ashoka (IMF Working Papers; Working Paper ;, 2012)
Heightened uncertainty since the onset of the Great Recession has materially increased saving rates, contributing to lower consumption and GDP growth. Consistent with a model of precautionary savings in the face of uncertainty, we find for a panel of advanced economies that greater labor income uncertainty is significantly associated with higher household savings. These results are robust to controlling for other determinants of saving rates, including wealth-to-income ratios, the government fiscal balance, demographics, credit conditions, and global growth and financial stress. Our estimates imply that at least two-fifths of the sharp increase in household saving rates between 2007 and 2009 can be attributed to the precautionary savings motive.